FRI0469 The Additive Value of Nailfold Videocapillaroscopy Patterns to Disease-Specific Autoantibodies in Discrimination of Patients with Systemic Sclerosis at Risk for Severe Organ Involvement. (9th June 2015) - Markusse, I.; Meijs, J.; de Boer, B.; Bakker, J.; Schippers, P.; Schouffoer, A.; Ajmone Marsan, N.; Kroft, L.; Ninaber, M.; Huizinga, T.; de Vries-Bouwstra, J.
Abstract : Background: Severe nailfold videocapillaroscopy (NVC) patterns in patients with systemic sclerosis (SSc) are associated with a high risk of organ involvement. Previously, the association between anti-topoisomerase (anti-Scl70) and anti-centromere (ACA) and specific NVC patterns has been explored. Whether anti-ribonucleoprotein (anti-RNP) and anti-RNA polymerase III (anti-RNAP3) associate with specific NVC patterns, and whether the combination of different autoantibodies and NVC pattern contributes to better discrimination of patients at risk for organ involvement remains unclear. Objectives: To explore the association between clinical phenotype and the combination of autoantibodies and NVC pattern in a large cohort. Methods: For this cross-sectional study, data on NVC scleroderma patterns (early, active, late) and ACA, anti-Scl-70, anti-RNP and anti-RNAP3 were investigated in 287 patients of the Leiden Systemic Sclerosis Cohort. Logistic regression analysis, with NVC pattern and autoantibodies as independent and disease characteristic as dependent variables were performed, adjusted for age, disease duration and the use of immunosuppressive or vasoactive drugs. Under the assumption of a linear relationship within NVC patterns from mild to severe, it was entered as a continuous variable in the order: no specific SSc pattern, early, active and late pattern. A separate analysis was performed for each autoantibody and each clinical feature. Results: 253/287 patients (88%) had a specific scleroderma NVC pattern; 29 (10%) early, 121 (42%) active and 103 (36%) late pattern. 107 patients (37%) were ACA positive (+), 69 patients (24%) were anti-Scl-70+, 26 patients (9%) were anti-RNP+ and 13 patients (5%) were anti-RNAP3+. The table shows the associations between NVC pattern sand clinical features stratified for autoantibody. Conclusions: Strikingly, the association between NVC pattern and clinical features was stable and independent of specific autoantibodies. Even in ACA+ patients severe NVC patterns were associated with lung involvement. These data suggest that the combination of NVC pattern and autoantibodies contributes to discrimination of SSc patients that need extensive organ screening and follow-up. Disclosure of Interest: I. Markusse: None declared, J. Meijs Grant/research support from: unrestricted educational grant of Actelion Pharmaceuticals Nederland BV (Woerden, The Netherlands), B. de Boer: None declared, J. Bakker: None declared, P. Schippers: None declared, A. Schouffoer: None declared, N. Ajmone Marsan: None declared, L. Kroft: None declared, M. Ninaber: None declared, T. Huizinga: None declared, J. de Vries - Bouwstra: None declared